Seleksi dan Kemajuan Seleksi Karakter Komponen Hasil pada Persilangan Cabai Keriting dan Cabai Besar - ,, Yunandra; Syukur, Muhamad; Maharijaya, dan Awang (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2017)
Selection is very important activity in plant breeding program. The purpose of this study was to obtain genetic information, heritability and expected genetic advance, and to compare the genetic advance expectations with the selection advance. The research was conducted from September 2013 to November 2015 at Research Station of Leuwikopo, Dramaga, Bogor. Distribution of F2 population data in this study was broader than that of F3 populations. Broad sense heritability estimated by F3 populations showed in agreement to that estimated by F2 population. Character of fruit weight, fruit length, pedicel length and yield had positive value of selection advance appropriate to the genetic advance expectations in F2 populations. The value of heritability estimate and genetic advance were high indicating that the phenotypic variances were controlled by action of additive genes.Keywords: genetic advance, heritability, selection advance